2009
DOI: 10.1002/jcla.20325
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin antibodies in the sera of patients with diagnosed chronic fatigue syndrome

Abstract: Examination of anticardiolipin antibodies (ACAs) in the sera of patients clinically diagnosed with chronic fatigue syndrome (CFS) using an enzyme-linked immunoassay procedure demonstrated the presence of immunoglobulin M isotypes in 95% of CFS serum samples tested. The presence of immunoglobulin G and immunoglobulin A isotypes were also detected in a subset of the samples. Future studies will focus on elucidating whether alterations to mitochondrial inner membranes and/or metabolic functions play a possible ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Our observation is supported by a study that showed raised aCL IgG in young women aged between 36 and 37 years who had suffered ischemic stroke without having hypertension and hyperlipidemia (Cojocaru et al., 2007). Besides air pollution, chronic fatigue (Hokama et al., 2009) and mental health problems like schizophrenia can raise aCL level (Halacheva et al., 2009). Chronic fatigue in biomass‐using women is a distinct possibility, because they have the dual responsibility of fuel collection/preparation and cooking.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation is supported by a study that showed raised aCL IgG in young women aged between 36 and 37 years who had suffered ischemic stroke without having hypertension and hyperlipidemia (Cojocaru et al., 2007). Besides air pollution, chronic fatigue (Hokama et al., 2009) and mental health problems like schizophrenia can raise aCL level (Halacheva et al., 2009). Chronic fatigue in biomass‐using women is a distinct possibility, because they have the dual responsibility of fuel collection/preparation and cooking.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may cause mutagenic mtDNA lesions and accumulations of these lesions [19]. ME/CFS has been shown to be accompanied by mitochondrial damage [10,11,20,21] and mitochondrial dysfunctions and structural changes [22,23], which is important in that these mitochondrial and mtDNA lesions may cause lowered activity of the mitochondrial respiratory chain, which produces ATP and accounts for 98% of cellular energy [19]. …”
Section: Backgroiundmentioning
confidence: 99%
“…Anti-cardiolipin antibodies have been documented in 95% of patients with CFS in one study 132. In CFS triggered by parvovirus B19, antinuclear antibody and RF were detectable in serum 133…”
Section: Autoimmune Diseases Associated With Parvovirus B19 Infectionmentioning
confidence: 90%